Enhancing economic growth through financial inclusion: An ARDL analysis / Shahiszan Ismail and Jamilah Laidin - Ismail, Shahiszan; Laidin, Jamilah (Research Management Centre (RMC), 2023)
This study explores the crucial relationship between financial inclusion and economic growth, which has become a primary focus for policymakers, economists, and development practitioners worldwide. Financial inclusion aims to provide fair and unrestricted access to financial services, particularly for marginalised populations without traditional banking access. This study investigates how financial inclusion promotes economic growth by empowering individuals and businesses, fostering financial security, and stimulating entrepreneurship, innovation, and investment. Using rigorous analysis methods, the Autoregressive Distributed Lag (ARDL) approach, this study examines the cointegration effect between financial inclusion and economic growth in Malaysia's short- and long-term perspectives. The results indicate a positive impact of financial inclusion on economic growth, mainly through the number of mobile and internet banking transactions (MOBILE), Automatic Teller Machines (ATM), and the number of institutions of commercial banks (ICB). However, compared to other financial inclusion proxies, ICB shows a stronger association with long-term economic growth. Similarly, the initial income (A), trade openness (TRADE), and capital (K) significantly contribute to economic growth in the long run. Interestingly, labour appears to adversely affect economic growth in the long run for both Model 1 and 2. This phenomenon could be attributed to fluctuations in labour market conditions, including changes in workforce skill levels or demographic shifts. The findings underscore the transformative potential of financial inclusion in achieving sustainable development and poverty reduction.